A new Anagyrus (Hymenoptera: Encyrtidae) from Argentina, parasitoid of Hypogeococcus sp. (Hemiptera: Pseudococcidae) on Harrisia pomanensis (Cactaceae) - Triapitsyn, Serguei V.; Aguirre, María B.; Logarzo, Guillermo A. (Zootaxa, 2016)
A new species of Anagyrus Howard (Hymenoptera: Encyrtidae), A. lapachosus sp. n., is described from Salta Province of Argentina as a parasitoid of Hypogeococcus sp. (Hemiptera: Pseudococcidae) on Harrisia pomanensis cactus (Cactaceae). It is a candidate “new association” biological control agent for quarantine evaluation and possible following introduction to Puerto Rico (USA) against another Hypogeococcus sp., commonly called the Harrisia cactus mealybug and often misidentified as H. pungens Granara de Willink (according to our unpublished data the latter attacks only Amaranthaceae), which devastates or threatens the native cacti there and also in some other Caribbean islands (Triapitsyn, Aguirre et al. 2014; Carrera-Martínez et al. 2015).